L-arginine Attenuates Oxidative Stress and Regulates the Inflammatory Actions of Tumor Necrosis Factor and Interleukin-10 in a Rat Model of Pre-eclampsia (African Journal of Biomedical Research, 2019)
Maternal endothelial dysfunction, oxidative stress and inflammation are parts of the theories associated with preeclampsia. Larginineis the natural substrate for NO synthase and responsible for the production of NO, This study investigated the effect ofL-arginine on blood pressure, oxidative stress and inflammatory markers in pregnant rats administered N-nitro-arginine methylester (L-NAME). Thirty-six nulliparous female Sprague-Dawley rats weighing between 150-170 g were divided into 4 groupsas follows: control (normal saline), L-NAME (50mg/kg b.w. intraperitoneal injection from days 13-18 of pregnancy), L-NAME+ L-arginine (50mg/kg b.w. and 1g/kg b.w. of L-arginine from days 13-18 of pregnancy) and L-arginine (1g/kg b.w. administeredorally from days 13-18 of pregnancy). Fetal outcome and blood pressure were measured on day 19 of pregnancy. The placentawas homogenized for oxidative enzyme assay and serum nitric oxide metabolite (NOx), endothelial nitric oxide synthase (eNOS),tumor necrosis factor-α (TNF-α) and interleukin-10 (IL-10) levels were measured. L-arginine reduced blood pressure increaseby L-NAME. It also reduced placenta malondialdehyde level and increased glutathione peroxidase level thereby countering theeffects of L-NAME. It increased eNOS and NOx levels and decreased TNF-α level compared with L-NAME. L-argininesupplementation in rat pregnancy prevents increase in blood pressure by improving eNOS and NOx levels thereby reducingoxidative stress and reducing proinflamatorry actions of TNF-α.